Functional neurological evaluation of the brainstem. Part I: the blink reflex Evaluación neurofuncional del tallo cerebral. Parte I: Reflejo del parpadeo - Jaime Bedoya; Claudia Gutiérrez; Fidias E. Leon Sarmiento (Iatreia, 2009)
The blink reflex is the neural response elicited in the orbicular oculi muscle after single or paired supraorbital nerve stimulation, by either electrical, mechanical, acoustic, thermal, chemical or magnetic stimulation. It is made up of three responses called R1, R2 and R3. R1 is an early response that follows A beta fibers, and does not habituate. R2 is a middle-latency response that follows A beta and A delta fibers, tends to habituate and is modulated by sensorimotor suprasegmental structures. R3 is a long-latency response, generated by stimulation of a multisynaptic chain of neurons that involve type C fibers belonging to a complex pontothalamic-amigdalo-cerebellar pathway. It is also possible to record three silent periods if the blink reflex is obtained while the subject makes a voluntary facial muscle effort. The functional study of this reflex allows to define with certainty whether the lesion is in afferent or efferent pathways or if it involves an abnormal sensorimotor integration due to disorders of the central, autonomic or peripheral nervous systems. A correct execution of these studies, and their appropriate interpretation, based on the underlying mechanisms of neural plasticity, will guide toward better neurorehabilitation protocols. El reflejo de parpadeo es la respuesta neural que se obtiene en el músculo orbicular de los ojos, luego de estimular el nervio trigeminal, bien sea de manera simple o pareada, por medios eléctricos, mecánicos, acústicos, térmicos, químicos o magnéticos; cuando se estimula dicho nervio se obtienen tres respuestas llamadas R1, R2 y R3. R1 tiene latencia corta, viaja por fibras A beta y no se habitúa. R2 es de latencia mediana, viaja por fibras A beta o A delta, tiende a habituarse y la modulan estructuras suprasegmentales sensorimotoras. R3 es de latencia larga, se genera al estimular vías multisinápticas que involucran fibras tipo C, en una ruta compleja ponto-amígdalo-talámico-cerebelar. También se pueden registrar tres períodos silentes cuando el reflejo del parpadeo se obtiene mientras el individuo hace una contracción voluntaria muscular facial. El estudio funcional de este reflejo permite identificar con certeza si la lesión está en las vías aferentes o en las eferentes o si involucra una integración anormal sensorimotora debida a trastornos de los sistemas nerviosos central, autonómico o periférico. La ejecución correcta de estos estudios, así como su interpretación apropiada, con base en los mecanismos subyacentes de plasticidad neural, son guías para orientar mejor los protocolos de neurorrehabilitación.